2015
DOI: 10.1177/0268580915578745
|View full text |Cite
|
Sign up to set email alerts
|

Explaining participation in the informal economy: An institutional incongruence perspective

Abstract: Drawing inspiration from institutional theory, a small sub-stream of literature has proposed that participation in the informal economy arises from the lack of alignment of a society's formal institutions (i.e., its codified laws and regulations) with its informal institutions (i.e., the norms, values and beliefs of its population). To further advance this explanation, this paper reports a 2013 Eurobarometer survey involving 27,563 face-to-face interviews across 28 European countries. The finding is that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 68 publications
5
66
0
Order By: Relevance
“…Therefore, a general acceptance (tolerance) to corruption was considered one of the main causes behind widespread informal payments in health care . Other causes can be suggested by the degree of asymmetry between the codified laws and regulations of the formal institutions and the unwritten socially shared rules of informal institutions or the grade of un‐alignment between formal and informal institutions, which tends to strongly associate with participation in the informal economy …”
Section: Introduction Explaining Informal Payments In Health Carementioning
confidence: 99%
“…Therefore, a general acceptance (tolerance) to corruption was considered one of the main causes behind widespread informal payments in health care . Other causes can be suggested by the degree of asymmetry between the codified laws and regulations of the formal institutions and the unwritten socially shared rules of informal institutions or the grade of un‐alignment between formal and informal institutions, which tends to strongly associate with participation in the informal economy …”
Section: Introduction Explaining Informal Payments In Health Carementioning
confidence: 99%
“…; Williams ; Williams and Padmore ; Williams et al . ; Flórez and Perales ). In an evaluation of cross‐national levels of informal employment in the European Union, Williams (, p. 491) found that reducing informal employment required, among other things, higher expenditure on labor market interventions and social protection.…”
Section: Discussionmentioning
confidence: 98%
“…Institutional theory recognises the coexistence of both formal and informal markets (Williams, Horodnic and Windebank 2015) and when applied to a changing PRS provides a useful framework for understanding how markets fragment to cater for and/or exploit different segments and needs. Institutional theory also posits that governments will act to minimise the adverse impact of markets through regulation, direct subsidises and programs which support people to participate in or access markets rather than fundamentally replacing them to meet welfare needs.…”
Section: Conceptualising Prs Intermediary Pathwaysmentioning
confidence: 99%